Heat Shock Protein 47 Promotes Glioma Angiogenesis. (7th May 2015) - Wu, Zhe Bao; Cai, Lin; Lin, Shao Jian; Leng, Zhi Gen; Guo, Yu Hang; Yang, Wen Lei; Chu, Yi Wei; Yang, Shao‐Hua; Zhao, Wei Guo
Abstract: Heat shock protein 47 (HSP47) is a collagen‐binding protein, which has been recently found to express in glioma vessels. However, the expression profile of HSP47 in glioma patients and the underlying mechanisms of HSP47 on glioma angiogenesis are not fully explored. In the current study, we found that expression of HSP47 in glioma vessels was correlated with the grades of gliomas. HSP47 knockdown by siRNAs significantly decreased cell viability in vitro and tumor volume in vivo ; moreover, it reduced the microvessel density (MVD) by CD31 immunohistochemistry in vivo . HSP47 knockdown significantly inhibited tube formation, invasion and proliferation of human umbilical vein endothelial cells (HUVECs). Furthermore, conditional medium derived from HSP47 knockdown cells significantly inhibited HUVECs tube formation and migration, while it increased chemosensitivity of HUVECs cells to Avastin. Silencing of HSP47 decreased VEGF expression in glioma cells consistently, and reduced glioma vasculature. Furthermore, HSP47 promoted glioma angiogenesis through HIF1α‐VEGFR2 signaling. The present study demonstrates that HSP47 promotes glioma angiogenesis and highlights the importance of HSP47 as an attractive therapeutic target of GBM.